Decision-making and power in the British Conservative Party a study of the Indian problem 1929-1934 - Ghosh, S.C. (Suresh Chandra) (Calcutta Oceania Publishing House, 1972)
The book makes an original theoretic contribution to the study of the decision-making and power in a large political party. With a focus on decision-making, with a detailed study of the Conservatives' dissensions on the Indian problem since 1917, the author shows that the distribution of power in the British Conservative Party is diffused and tends to be specific to issues, and that the power-situation is made complex and obscure by the active participation of people and interests other than the formal followers in a given decision-making process.

In the second place, it makes an attempt to contribute to the study of a major political decision. It makes an analysis of actors (the leaders, rank and file, factions and pressures groups, including a big business) involved, and describes how the process of interaction affected the decision.

In the next place, the book constitutes an important chapter in the history of the British Commonwealth of Nations. It shows that what was involved in the controversy was undoubtedly the greatest constitutional problem that the Empire faced--the problem of the extension of the Commonwealth principle for the first time to a people of different race, colour, religions, and way of life. The Conservative leader, Stanley Baldwin, was convinced that Britain should make it clear that the goal of British policy in India was Dominion Status, but because of the opposition of Sir Winston Churchill and others, and the apprehensions of the bulk of the conservatives, he failed to commit his party and Britain to this undertaking.

Apart from a detailed study of the Conservatives' dissensions which affected the Government of India Act, 1935, it shows that the conservatives' opposition to the Montagu-Chelmsford Reforms, 1919 found expression on the Dyer-incident. In short, the book explodes the myth that the ultimate goal of the British policy was set at rest either by the Montagu declaration of 1917 or by Irwin's announcement of 1929. Nevertheless, the debates and discussions in the thirties made the conservatives ponder over the fact that the Empire could not be held together except by the ideal of a multi-racial Commonwealth of Nations.--Provided the author.
Includes bibliographical references (pages [209]-220) and index.
Keywords: Conservative Party (Great Britain); Great Britain -- Colonies -- India; India -- Constitutional history; India -- Politics and government -- 1919-1947.